1977
DOI: 10.1083/jcb.72.3.714
|View full text |Cite
|
Sign up to set email alerts
|

Two fractions of rough endoplasmic reticulum from rat liver. I. Recovery of rapidly sedimenting endoplasmic reticulum in association with mitochondria.

Abstract: Low-speed centrifugation (640 g) of rat liver homogenates, prepared with a standard ionic medium, yielded a pellet from which a rapidly sedimenting fraction of rough endoplasmic reticulum (RSER) was recovered free of nuclei. This fraction contained 20-25% of cellular RNA and approximately 30% of total glucose-6-phosphatase (ER marker) activity. A major portion of total cytochrome c oxidase (mitochondrial marker) activity was also recovered in this fraction, with the remainder sedimenting between 640 and 6,000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0
1

Year Published

1981
1981
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(79 citation statements)
references
References 26 publications
3
75
0
1
Order By: Relevance
“…The existence of anchorage sites between ER and mitochondria have been suggested based on co-sedimentation of ER particles with mitochondria and electron microscopic observations of close associations between mitochondria and ER vesicles [151,152]. Recent studies of the ER-mitochondrial interface by electron tomography and by limited proteolysis provided evidence for direct protein linkage (tethers) between both rough and smooth ER and mitochondria.…”
Section: Physical Linkage Between Er and Mitochondriamentioning
confidence: 99%
“…The existence of anchorage sites between ER and mitochondria have been suggested based on co-sedimentation of ER particles with mitochondria and electron microscopic observations of close associations between mitochondria and ER vesicles [151,152]. Recent studies of the ER-mitochondrial interface by electron tomography and by limited proteolysis provided evidence for direct protein linkage (tethers) between both rough and smooth ER and mitochondria.…”
Section: Physical Linkage Between Er and Mitochondriamentioning
confidence: 99%
“…MCSs have been observed by both biochemical methods and electron microscopy in mammalian, yeast, fly, and plant cells (Shore and Tata 1977;Perkins et al 1997;Ladinsky et al 1999). These dynamic structures are highly enriched in lipid biosynthetic enzymes and LTPs, and are generally formed and/or stabilized by specialized tethering proteins (Fig.…”
Section: Nonvesicular Lipid Transportmentioning
confidence: 99%
“…Structural interactions between SR/ER and mitochondria in different cell types A close association between ER and mitochondria was initially described in electron microscopy images of liver tissue (Morré et al, 1971;Shore and Tata, 1977). A stable interorganellar interaction was indicated when tissue fractionation studies revealed an ER membrane contamination in isolated mitochondria, referred to as mitochondria-associated membranes (MAMs) (Vance, 1990).…”
Section: Introductionmentioning
confidence: 99%